Anticipation of Difficult Airway by Neck Circumference to Thyromental Distance Ratio - Rejin Kumar Udaya; Saba Khan; Laxmi Pathak; Pradip Chhetri (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Unanticipated difﬁcult intubation scenario is a major concern for anaesthetists which contributes to perioperative morbidity and mortality. Characteristics of difﬁcult intubation indices like increased neck circumference (NC) and reduced thyromental distance (TM) when combined as a ratio can increase accuracy in predicting difﬁcult intubation. MATERIAL AND METHODS This prospective, observational study was conducted at Universal College of Medical Sciences Teaching Hospital on 160 patients of ASA class I and II planned for surgery under general anaesthesia with endotracheal intubation. Airway indices measured were modiﬁed mallampati classiﬁcation (MM), thyromental distance, neck circumference, and neck circumference to thyromental distance ratio (NC/TM). RESULTS NC/TM showed the highest sensitivity, speciﬁcity, PPV and NPV in the non-obese group (p <0.001) as compared to MM, NC and TM. In the obese group, NC/TM showed the highest sensitivity, PPV and NPV (p <0.001) as compared to NC and TM while the speciﬁcity was highest and similar to MM as compared to NC and TM. CONCLUSION Neck circumference to thyromental distance ratio is a better predictor of anticipating difﬁcult intubation in both obese and non-obese patients compared to modiﬁed mallampati classiﬁcation, thyromental distance and neck circumference.